Associations between aerobic fitness, negative symptoms, cognitive deficits and brain structure in schizophrenia - a cross-sectional study - Maurus, Isabel; Röll, Lukas; Keeser, Daniel; Karali, Temmuz; Papazov, Boris; Hasan, Alkomiet; Schmitt, Andrea; Papazova, Irina; Lembeck, Moritz; Hirjak, Dusan; Thieme, Cristina E.; Sykorova, Eliska; et al. (Schizophrenia, 2022)
Negative symptoms and cognitive deficits are common in individuals with schizophrenia, greatly affect their outcome, and have been associated with alterations in cerebral gray and white matter volume (GMV, WMV). In the last decade, aerobic endurance training has emerged as a promising intervention to alleviate these symptoms and improved aerobic fitness has been suggested as a key moderator variable. In the present study, we investigated, whether aerobic fitness is associated with fewer cognitive deficits and negative symptoms and with GMVs and WMVs in individuals with schizophrenia in a cross-sectional design. In the largest study to date on the implications of fitness in individuals with schizophrenia, 111 participants at two centers underwent assessments of negative symptoms, cognitive functioning, and aerobic fitness and 69 underwent additional structural magnetic resonance imaging. Multilevel Bayesian partial correlations were computed to quantify relationships between the variables of interest. The main finding was a positive association of aerobic fitness with right hippocampal GMV and WMVs in parahippocampal and several cerebellar regions. We found limited evidence for an association of aerobic fitness with cognitive functioning and negative symptoms. In summary, our results strengthen the notion that aerobic fitness and hippocampal plasticity are interrelated which holds implications for the design of exercise interventions in individuals with schizophrenia.